2018
DOI: 10.21521/mw.5966
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of oral immunization of free-living foxes in the reduction of rabies in Poland in 2011-2015

Abstract: SummaryThe paper presents the epidemiological situation of rabies in Poland in the period of 2011-2015, as well as discusses the effectiveness and costs of a national campaign of oral immunization of free-living foxes that has been carried out since 2002. It also evaluates the impact of the preventive measures on the dynamics of the number of foxes. During the study period, a decrease in the number of confirmed rabies cases in wild and domestic animals was recorded, but the primary reservoir of the virus conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Another, not less important, element that directly affects the dynamics of the number of hares is predation. The use of oral treatments for immunization of free-living foxes eliminated one of the basic factors limiting the population, which in turn increased the impact of this species on small animals (Demirbas, 2015;Gołdyn, et al, 2003;Goszczyński and Wasilewski, 1992;Panek et al, 2006;Wasilewski, 2007;Flis et al, 2017Flis et al, , 2018. Hušek et al (2015) a high rate of fox predation targeting hares depending on the habitat and reported that hare males tend to fall as a prey.…”
Section: Introductionmentioning
confidence: 99%
“…Another, not less important, element that directly affects the dynamics of the number of hares is predation. The use of oral treatments for immunization of free-living foxes eliminated one of the basic factors limiting the population, which in turn increased the impact of this species on small animals (Demirbas, 2015;Gołdyn, et al, 2003;Goszczyński and Wasilewski, 1992;Panek et al, 2006;Wasilewski, 2007;Flis et al, 2017Flis et al, , 2018. Hušek et al (2015) a high rate of fox predation targeting hares depending on the habitat and reported that hare males tend to fall as a prey.…”
Section: Introductionmentioning
confidence: 99%